(untitled) (ENTHYMEMA, 2020)
If on a Winter’s Night a Traveler represents the natural outcome of a creative path that, from a certain point on, exhibits a marked metaliterary inclination: the original narrative experiment of 1979 brings this tone to saturation, collecting multiple complex metatextual strategies that confuse the levels of reality (to use the title of a Calvino’s essay) and at the same time the identity of author, narrator and character. The result is an elaborate and flooring structure which, while taking up re-elaborating and combining procedures already present in some texts by Borges and Nabokov (authors admittedly dear to Calvino), identifies its closest precedent (even temporally) in La tia Julia y el escribidor (1977) by Mario Vargas Llosa.